Pengaruh Media Pizza Slice pada Pembelajaran Matematika terhadap Hasil Belajar Siswa Kelas II SD Al Maksum Paya Geli - Khadijah, Khadijah Khadijah (Universitas Muria Kudus, 2025)
This study aims to determine the effect of pizza slice media on mathematics learning outcomes in fraction material. The type of research used is Quasy Experimental. The population in this study were all school students at SD Al Maksum Paya Geli in the 2023/2024 Academic Year in the even semester totaling 20 students. Data analysis techniques are descriptive statistical analysis and inferential statistical analysis. Based on the results of the study, it can be concluded that the learning process that took place during two meetings and was observed using a learning process implementation sheet using pizza slice media, the results obtained showed progress in each meeting and were categorized as effective. The mathematics learning outcomes of students in the experimental class and control class were good and sufficient. The average value of the control class was 42.00 and the experimental class was 85.50. After the hypothesis test was carried out and analyzed, the results obtained were that there was a significant effect of the application of pizza slice media on the mathematics learning outcomes of class II students of SD Al Maksum Paya Geli, Sunggal District, Deli Serdang Regency.